2019
DOI: 10.1128/aem.02032-18
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbial Divergence between Two Populations of the Hadal Amphipod Hirondellea gigas

Abstract: Hadal environments sustain diverse microorganisms. A few studies have investigated hadal microbial communities consisting of free-living or particle-associated bacteria and archaea. However, animal-associated microbial communities in hadal environments remain largely unexplored, and comparative analyses of animal gut microbiota between two isolated hadal environments have never been done so far. In the present study, 228 Gb of gut metagenomes of the giant amphipodHirondellea gigasfrom two hadal trenches, the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 43 publications
2
17
1
Order By: Relevance
“…In detail, the functional pathways of PTS, Glycolysis/Gluconeogenesis, Homologous Recombination, Bacterial Chemotaxis, and Flagellar Assembly were detected as the common functional types in all the amphipod gut samples, suggesting that the existence of a set of similar functional components in gut microbes of the hadal amphipod species ( Figure 4 and Supplementary Figures 1 , 2 ). However, the previous study on the H. gigas from Mariana Trench and Japan Trench have shown that different geographical locations lead to functional differentiation of their gut microbes ( Zhang et al, 2019 ) and which was inconsistent with the results of the present study. This difference may result from a combination of selection factors, such as habitat environment, microbial interaction, and host genetic background, and the details remain to be analyzed.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In detail, the functional pathways of PTS, Glycolysis/Gluconeogenesis, Homologous Recombination, Bacterial Chemotaxis, and Flagellar Assembly were detected as the common functional types in all the amphipod gut samples, suggesting that the existence of a set of similar functional components in gut microbes of the hadal amphipod species ( Figure 4 and Supplementary Figures 1 , 2 ). However, the previous study on the H. gigas from Mariana Trench and Japan Trench have shown that different geographical locations lead to functional differentiation of their gut microbes ( Zhang et al, 2019 ) and which was inconsistent with the results of the present study. This difference may result from a combination of selection factors, such as habitat environment, microbial interaction, and host genetic background, and the details remain to be analyzed.…”
Section: Discussioncontrasting
confidence: 99%
“…For instance, Candidatus Hepatoplasma was detected as the dominant bacterium in the gut of the S. schellenbergi and A. gigantea , whereas relative absence in the H. gigas. Given that the New Britain Trench is closest to the coast followed by the Marceau Trench, and finally the Mariana Trench, the decaying plant material content in these trenches should show a decreasing trend, which may be the reason for the difference in the abundance of Candidatus Hepatoplasma in the gut of different amphipod species, and similar conclusions have been mentioned in previous studies ( Zhang et al, 2019 ). Moreover, the difference in the abundance of Psychromonas of gut microbial composition was also detected among the three geographically isolated amphipod species, especially the almost absence of Psychromonas in the S. schellenbergi and A. gigantea , which suggested that their function is dispensable or their counterparts have emerged in the guts of these amphipods, as Zhang et al (2019) mentioned in the previous study.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…[95]) and the microbial activity of the gut contents of deep-sea animals shows high levels of piezophily [131]. However, the genus Colwellia is not present in recognizable abundances within hadal amphipod metagenomes [154], their high % GC is not indicative of an endosymbiont [89], and the obligate piezophile Colwellia sp. TT2012 was isolated from sediments rather than amphipods.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in molecular ecological techniques, such as metagenomics, have enabled a more efficient pathway to address the taxonomic and functional composition of marine microbiota, including the free-living bacterioplankton [1,2,3], the sediment-dwelling microbes [4,5,6], the surface-attached biofilms [7,8,9], and the animal-associated symbionts [10,11,12]. Pursuing the goal characterisng the global seawater microbiota, the Tara Oceans expedition collected seawater samples from 68 locations, representing all main oceanic regions, and performed metagenomics to study the structure and function of the global ocean microbiota [1].…”
Section: Introductionmentioning
confidence: 99%